30. PRACTICE OF HEALTH REPORT STATISTICS AMONG COMMUNE HEALTH STATION STAFF IN HAU LOC AND QUANG XUONG DISTRICTS, THANH HOA PROVINCE, 2024, AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the practice of medical statistical reporting among healthcare staff at commune health stations in Hau Loc districts and Quang Xuong districts, Thanh Hoa province, and to analyze related factors.Objects and methods: A cross-sectional study was conducted at 48 commune health stations in the two districts from January 2024 to February 2025. Data were collected using a standardized questionnaire developed based on health sector circulars on medical statistical reporting and expert opinions.Results: Among 219 healthcare staff surveyed, 91.3% demonstrated good practice in medical statistical reporting. The proportion of good practice was significantly higher in Quang Xuong district compared to Hau Loc district (67% vs. 33%, p = 0.003). No statistically significant differences were observed between demographic factors such as age, gender, professional qualifications, and years of experience with the rate of good practice.Conclusion: The rate of good practice in medical statistical reporting among healthcare staff at commune health stations was high, particularly in Quang Xuong district. Demographic factors did not significantly associate with the rate of good practice in the two districts.
Keywords: Health report statistics; practice; primary healthcare; Thanh Hoa; logistic regression.